The Problem of Child Labor in the Works of Gʻafur Gʻulom - Abdixoliqova , Ruxshona (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the problem of child labor in the works of Gʻafur Gʻulom from both artistic and social perspectives. In particular, the story Shum bola and other works by the writer reveal how children are forced to work at an early age due to difficult social conditions, are deprived of educational opportunities, and face poverty and social inequality. The article examines the causes of child labor, its impact on children’s fate and future, and its connection with illiteracy and poverty through comparative analysis. The issue of child labor is also compared with the modern era and legal norms, and conclusions are drawn about protecting children’s rights and ensuring their right to education. The article argues that child labor is a social problem that negatively affects the development of society and that education and enlightenment are important factors in overcoming it.